2013
DOI: 10.1007/s00408-013-9471-7
|View full text |Cite
|
Sign up to set email alerts
|

Intima-Media Thickness in Patients With Obstructive Sleep Apnea Without Comorbidities

Abstract: BackgroundObstructive sleep apnea (OSA) is associated with elevated risk of cardiovascular events. The early stages of vascular complications can be visualized by means of ultrasound. Intima-media thickness (IMT) correlates with the presence of risk factors of cardiovascular diseases such as hypertension, diabetes, tobacco smoking, or hyperlipidemia. However, little is known whether OSA itself may be the cause of IMT thickening.MethodsThe study group was composed of 28 patients (6 women, 22 men; mean age = 53.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
7
0
1
Order By: Relevance
“…Previous research indicates that quantitative IMT and QAS techniques, as noninvasive examinations, provides a comprehensive evaluation of CCA remodeling for assessing preclinical atherosclerosis and early-stage diabetes (15,16,30). Although several studies have shown that there are no changes in carotid IMT in OSA patients compared to non-snorers (13,31), substantial evidence indicates a significant increase in OSA patients compared to non-snorers (32). In this study, we creatively used the ultrasound radiofrequency technology to detect changes in the structure and function of the carotid artery in OSA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicates that quantitative IMT and QAS techniques, as noninvasive examinations, provides a comprehensive evaluation of CCA remodeling for assessing preclinical atherosclerosis and early-stage diabetes (15,16,30). Although several studies have shown that there are no changes in carotid IMT in OSA patients compared to non-snorers (13,31), substantial evidence indicates a significant increase in OSA patients compared to non-snorers (32). In this study, we creatively used the ultrasound radiofrequency technology to detect changes in the structure and function of the carotid artery in OSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the values of arterial stiffness and compliance [pulse wave velocity (PWV) and carotid distensibility coefficient (DC)] are useful indices for predicting the future risk of cardiovascular events such as stroke and coronary heart disease (9,10). Increased IMT in OSA patients has been widely demonstrated (11)(12)(13)(14). Innovations in ultrasound technology, such as the US radiofrequency (RF)-data technology, allow for an automatic and accurate measurement of carotid IMT and arterial elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with some previous studies. Gorzewska et al 29 studied 28 nonobese OSA patients with no history of cardiovascular disease or significant abnormalities in glucose, hemoglobin A1c, and lipids. No significant differences were reported in carotid IMT between OSA cases and controls, and there were no associations between IMT versus AHI and the level of oxygen desaturation.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid intima‐media thickness (IMT) is a good indicator of the severity of atherosclerotic disease (O'Leary et al ., ) and can be a useful marker for the early stage of atherosclerosis (O'Leary and Polak, ). For research on risk factors for increased IMT in patients with OSA (Baguet et al ., ; Ciccone et al ., ; Gorzewska et al ., ; Kostrzewska et al ., ; Minoguchi et al ., ; Silvestrini et al ., ; Suzuki et al ., ), most previous studies had relatively small numbers of patients (Drager et al ., ; Gorzewska et al ., ; Minoguchi et al ., ) and less strict selection, and included patients lacking a polysomnography (PSG) diagnosis and those with several underlying diseases (Thunstrom et al ., ).…”
Section: Introductionmentioning
confidence: 99%